Endodontic Management of Mandibular Second Premolar with Vertucci Root Canal Configuration Type V - Shahzad Ali Shah (Case Reports in Dentistry)
The diversity of root canal anatomy in permanent dentition is quite common. Understanding the basic anatomy of the root canal morphology and its variations is particularly important for successful root canal treatment. Mandibular second premolar usually consists of a single root with a single root canal. The presence of split roots in the apical third of the root with two separate root canals is quite rare. The major cause of endodontic failure in missed canals is that it harbors bacteria and other microorganisms. Careful radiographic interpretation and clinical examination of the pulp chamber will be helpful in locating canal orifices. The mandibular premolars with Vertucci type V canal configuration pose a challenge in clinical management. Identifying them early is important to aid appropriate modification in treatment protocol. In this case report, important modifications of clinical steps and application of magnification for successful management with access chamber modification are explained.